Outcome of fetuses with soft markers: results of 3016 cases in Ahvaz city - Masihi, Sara; Barati, Mojgan; Karimi Moghaddam, Elham; Rezazadeh, Afshin; Ronaghi, Fatemeh (Medical journal of the Islamic Republic of Iran, 2021)
Although soft markers may be seen as normal variants, they are important due to their association with chromosomal and congenital abnormalities. This cross-sectional descriptive-analytical study was done on 3016 women who referred for perinatal care. Fetuses with any of soft markers including thickened nuchal fold (TNF), mild pyelectasis (MP), choroid plexus cyst (CPC), single umbilical artery (SUA), mega cisterna magna (MCM) and mild ventriculomegaly (MVM) were followed during pregnancy and birth. Data analysis was carried out using SPSS for Windows (version 22). Data were analyzed using chi-square and T-test. A p-value <0.050 was considered statistically significant. 285 (9.4%) fetuses with soft markers Including 148 (4.9%) fetuses with CPC, 118 (3.9%) fetuses with MP, 2 (0.1%,) fetuses with isolated TNF, 8 (0.3%) fetuses with isolated MVM, 4 (0.13%) fetuses with SUA, 4 (0.13%) fetuses with MCM were identified, and one fetus had TNF and MVM simultaneously. In cases with CPC, no abortion or major structural abnormalities were observed and all 148 neonates had normal phenotypes at birth. Among 118 cases with MP, one case had a major cardiac disorder, and 2 cases of abortions (1.7%) were reported (p=0.481). 83 cases (70.3%) were male and 35 cases (29.7%) were female (p=0.021) and all neonates had a normal phenotype. Both pregnancies with isolated TNF resulted in abortion. Of the 8 cases with isolated MVM, two cases had major structural abnormalities. 2 cases of abortion were reported and all infants had a normal phenotype. In one case, that fetus had TNF and MVM simultaneously. Amniocentesis showed no aneuploidy. No major structural abnormalities were observed in fetuses with SUA. One case of abortion was reported. Among the three births, two pre-term births were reported, and all three infants had normal phenotype. In four cases with MCM, no major structural abnormality was observed and all four neonates had normal phenotype. In cases without association with other structural abnormality, mothers who have fetuses with CPC or MP should be reassured that the pregnancy outcomes are generally favorable.